A case of Langerhans cell sarcoma on the scalp: Whole‐exome sequencing reveals a role of ultraviolet in the pathogenesis. Issue 11 (16th August 2020) - Katsuragawa, Hiroyuki; Yamada, Yosuke; Ishida, Yoshihiro; Kaku, Yo; Fujimoto, Masakazu; Kataoka, Tatsuki R.; Haga, Hironori
Abstract: Langerhans cell sarcoma (LCS) is a high‐grade neoplasm with overtly malignant cytological features and a Langerhans cell phenotype. The underlying genetic features are poorly understood, and only a few alterations, such as those of the MARK pathway‐related genes, CDKN2A and TP53 have been reported. Here we present a 70‐year‐old male with LCS on the scalp and pulmonary metastasis. The multinodular tumor, 3.0 cm in diameter, consisted of diffusely proliferated pleomorphic cells with numerous mitoses (53/10 HPFs). Immunohistochemically, the tumor cells were positive for CD1a, Langerin and PD‐L1, and the Ki‐67 labeling index was 50%. These pathological features were consistent with LCS, and were also observed in the metastatic tumor. Whole‐exome sequencing revealed that both the primary and metastatic tumors harbored a large number of mutations (>20 mutations/megabase), with deletion of CDKN2A and TP53 mutation, and highlighted that the mutational signature was predominantly characteristic of ultraviolet (UV) exposure (W = 0.828). Our results suggest, for the first time, that DNA damage by UV could accumulate in Langerhans cells and play a role in the pathogenesis of LCS. The high mutational burden and PD‐L1 expression in the tumor would provide a rationale for the use of immune checkpoint inhibitors for treatment of unresectable LCS.